The effect of concrete strength and fibre content on the fatigue performance of Ultra Thin Continuously Reinforced Concrete Pavement (UTCRCP) - Kearsley, Elsabe P. (University of Pretoria, 2017)
Dissertation (MEng)--University of Pretoria, 2017.